Embracing diversity through differentiated instruction in music education - Economidou Stavrou, Natassa (Frontiers in Education, 2024)
The article discusses the importance of differentiated instruction in music teaching and learning, emphasizing its role in fostering inclusivity and meeting the diverse needs of students. Drawing from personal teaching experiences, the author highlights how traditional, uniform teaching methods often neglect students’ varied readiness levels, learning profiles, and interests. Differentiated instruction, as conceptualized by Tomlinson, is presented as a proactive and flexible approach that tailors content, processes, products, and learning environments to cater to individual student needs. The article demystifies several myths about differentiation and discusses practical music classroom scenarios, illustrating how differentiation can address real-world challenges faced by music teachers. The conclusion advocates for the implementation of differentiated instruction as a non-negotiable, essential practice in music education, urging teacher educators to prepare future music teachers to engage every student meaningfully. The approach ensures a democratic and supportive music classroom where each student’s potential is recognized, nurtured, and celebrated.